Improving the safety of outpatient to Emergency Department transfers: A quality improvement study in a tertiary hospital in Pakistan - Aziza Lakhani; Samar Fatima; Areej Khawaja; Qurratulain Virani; Muzna Hashmi; Tehreem Khan; Khairunnissa Hooda (PLoS ONE, 2025)
Background Safe and coordinated patient transfers are essential for reducing morbidity, mortality, and adverse events. In outpatient clinics, early recognition of patient deterioration and standardized transfer protocols are key to enhancing safety. This quality improvement initiative addresses these gaps by ensuring the timely identification of critically ill patients, prompt management, and efficient transfer to the emergency department. Methods This study was conducted in two phases. In the pre-implementation phase (August 1–September 14, 2022), a multidisciplinary panel employed a modified Delphi method to revise early warning signs for critically ill clinic patients and developed a structured handoff tool to improve transfer communication. The tool was pilot tested and refined. The implementation phase (September 15–November 30, 2022) included hospital-wide training through webinars and in-person sessions, with effectiveness evaluated in forty staff members using pre- and post-training assessments. The quality initiative, comprising revised early warning criteria and standardized handoff documentation, was formally rolled out on December 1, 2022. Prospective data collection continued for one year (December 2022–November 2023) to evaluate the impact. Results Post-test scores demonstrated significant improvement in staff knowledge, particularly in identifying critically ill patients and initiating appropriate interventions. Among 268 patients requiring transfer, the majority (51.49%) were aged ≥60 years, and 56.3% were male. The most common presenting complaint was acute respiratory distress (31.7%). Compliance with the handoff tool was high (≥70% in 65.6% of cases). However, prolonged emergency department (ED) stays (>7 hours in 45.5% of cases) and a 5.2% mortality rate underscored ongoing challenges in patient flow and triaging. Conclusion Implementing structured transfer protocols, staff training, and standardized handoff tools can significantly improve patient transfer safety and efficiency in outpatient settings. However, further refinements, including enhanced triaging and digitizing documentation practices, are necessary for sustainable improvement. This project highlights the importance of systematic approaches in optimizing intra-hospital transfers in low-resource settings.